Design and performance of pre-stressed concrete railway sleepers containing fibres / Afidah Abu Bakar, Khafilah Din and Mat Som Marwi - Abu Bakar, Afidah; Din, Khafilah; Marwi, Mat Som (Institute of Research, Development and Commercialisation (IRDC), 2007)
The design of railway sleepers must account for irregularities of the train or the rails that generate dynamic loads. The sleepers could develop cracks during a train passage although not influential enough to disturb immediately the global track system. However, these cracks can pose a threat to the overall stiffness properties as they can propagate further under repeated loads induced by the train. Consequently they can cause fatigue, which is a structural failure at service condition. This will later constitute a major maintenance item if the problem is not properly addressed. It is intended that the application of highstrength concrete (HSC) with the inclusion of fibres in railway sleepers could reduce, delay or in certain conditions arrest the rate of crack growth. The design of sleeper was proven to comply in partial of the referenced Standards requirements. The fabrication works undertaken also proved that all procedures were followed satisfactorily and that the laboratory of the Faculty of Civil Engineering was able to handle the production. Structural tests carried out where loads were applied at rail seat showed that behaviour of HSFC sleepers had high flexural strength capacities due to the presence of fibres.